KETERLAKSANAAN PEMBELAJARAN HIGH ORDER THINKING SKILL (HOTS) PADA MATERI DINAMIKA ATMOSFER DAN DAMPAKNYA TERHADAP KEHIDUPAN (STUDI DI SMA PEMBANGUNAN LAB UNP DAN SMA PERTIWI 1 PADANG) - arif budiman; nofrion nofrion (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
This article was written to find out the feasibility or implementation of HOTS learning in terms of planning, implementation, and assessment aspects in the material of Atmospheric Dynamics and Its Impact in Life. This type of research is descriptive with a quantitative approach. The population of this research are all Class X IIS in SMA Pembangunan Laboratorium UNP and SMA Pertiwi 1 Padang. This research uses random sampling technique, namely Class X IIS 1 at SMA Pembangunan Laboratorium UNP and Class X IIS 2 at SMA Pertiwi 1 Padang. The results of the research show (1) in terms of lesson planning aspect, both schools are included in the very good category with a percentage of 93.75%. (2) in terms of learning implementation aspect in the ABD activities, both schools get good categories with a percentage between 75% -87%, while for ABL activities, SMA Pembangunan Laboratorium UNP gets a good category with a percentage between 76% -84% different from SMA Pertiwi 1 Padang which gets deficient and poor category with a percentage of 60% -67%. (3) in terms of learning assessment (LKPD) SMA Pembangunan Laboratorium UNP gets a percentage between 75% -100% better than SMA Pertiwi 1 which gets a percentage of 50% -83.3%.